The conservation status of Heard Island and the McDonald Islands - Keage, PL (1981)
For all its area, the subantarctic region has few land outcrops and those which do occur, with the exception of Heard Island and the McDonald Islands, have been extensively and irreversibly affected by human beings. As the last unspoilt unit representative of the subantarctic biome Heard Island and the McDonald Islands are of outstanding universal value. They contain unique natural features of exceptional beauty and host habitats of rare and endangered plant and animal species. With the cessation of sealing on Heard Island in the early 1900's, extreme geographic isolation and severity of climate have deterred visitors. The Islands are now experiencing increasing popularity and legal nature protection and conservation measures which can be considered to apply to the Islands are insufficient to ensure continuation of their biological integrity. This study draws attention to. the conservation status of subantarctic Heard Island and the McDonald Islands which are governed by Australia. Legal controls for the protection of nature on the Islands are assessed and contrasted with international conservation treaties and scientific programs which apply to the subantarctic region. It is concluded that the conservation status of the Islands is delicately balanced and that steps need to be taken as a matter of extreme urgency, to upgrade legal controls to facilitate their future protection. Practicable options available to government to afford appropriate protection to the Islands are identified and examined. These are: (a) introduction of new legislation; (b) incorporation of the Islands under the control of the Australian National Parks and Wildlife Service; or (c) incorporation of the Islands under the Antarctic Treaty (Environmental Protection) Act 1980. Of the three approaches, Option (c) is considered to be most beneficial for the Islands and would provide continuity between Antarctic and subantarctic nature conservation measures. The history, geography and biology of the Heard Island and the McDonald Islands are ...